2005
DOI: 10.1093/nar/gki916
|View full text |Cite
|
Sign up to set email alerts
|

Role of stacking interactions in the binding sequence preferences of DNA bis-intercalators: insight from thermodynamic integration free energy simulations

Abstract: The major structural determinant of the preference to bind to CpG binding sites on DNA exhibited by the natural quinoxaline bis-intercalators echinomycin and triostin A, or the quinoline echinomycin derivative, 2QN, is the 2-amino group of guanine (G). However, relocation of this group by means of introduction into the DNA molecule of the 2-aminoadenine (=2,6-diaminopurine, D) base in place of adenine (A) has been shown to lead to a drastic redistribution of binding sites, together with ultratight binding of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…[34] Firstly, solvent molecules and counterions were relaxed by energy minimization and allowed to redistribute around the positionally restrained solute (25 kcal mol À1 À2 ) during 50 ps of MD at constant temperature (300 K) and pressure (1 atm), essentially as described previously. [35] These initial harmonic restraints were gradually reduced in a series of progressive energy minimizations until they were completely removed. The resulting system, as well as those resulting from the hybrid QM/MM calculations described below, were heated from 100 to 300 K during 20 ps, equilibrated at 300 K for 1 ns and further simulated under the same conditions up to a total time of 10 ns during which system coordinates were collected every 20 ps for further analysis.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…[34] Firstly, solvent molecules and counterions were relaxed by energy minimization and allowed to redistribute around the positionally restrained solute (25 kcal mol À1 À2 ) during 50 ps of MD at constant temperature (300 K) and pressure (1 atm), essentially as described previously. [35] These initial harmonic restraints were gradually reduced in a series of progressive energy minimizations until they were completely removed. The resulting system, as well as those resulting from the hybrid QM/MM calculations described below, were heated from 100 to 300 K during 20 ps, equilibrated at 300 K for 1 ns and further simulated under the same conditions up to a total time of 10 ns during which system coordinates were collected every 20 ps for further analysis.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…[10] Later studies have shown that binding to specific bases is not only driven by hydrogen bonding, but that these compounds also search for the most favourable stacking interactions. [11] The difficulty to synthesize triostin A is exemplified by the fact that since its discovery more than 30 years ago, only two elegant, but tedious, solution chemistry syntheses, which involved purification at every intermediate, have been performed more than 20 years ago. [12] To elucidate the mode of action of this family of molecules, further biological studies require an efficient synthetic protocol.…”
mentioning
confidence: 99%
“…The Gln254 key residue interaction was conserved in all the peptidomimetics and known peptide inhibitor. More precise methods have been effectively anticipated for binding free energy calculation [29]. Regrettably, these approaches are not realistically available to rank the compounds, as these are computationally expensive.…”
Section: Mm-gbsa Binding Energy Calculationmentioning
confidence: 99%